2018
DOI: 10.1186/s13741-018-0084-9
|View full text |Cite
|
Sign up to set email alerts
|

What are the optimum components in a care bundle aimed at reducing post-operative pulmonary complications in high-risk patients?

Abstract: BackgroundPost-operative pulmonary complications (POPC) are common, predictable and associated with increased morbidity and mortality, independent of pre-operative risk. Interventions to reduce the incidence of POPC have been studied individually, but the use of a care bundle has not been widely investigated. The purpose of our work was to use Delphi consensus methodology and an independently chosen expert panel to formulate a care bundle for patients identified as being at high of POPC, as preparation towards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 46 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…Despite care bundles being strongly endorsed for prevention of ventilator associated pneumonia in intensive care,144145 evidence for equivalent non-ventilator bundles in perioperative patient care to prevent PPCs is still uncertain 146. An international Delphi consensus process considered which interventions might best be combined to reduce PPCs,147 and a UK based, patient centred quality improvement project (ERAS+) used a PPC reduction care bundle with notable success 148. To date, these care bundles have predominantly included relatively simple and inexpensive interventions, often with imperfect evidence of efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Despite care bundles being strongly endorsed for prevention of ventilator associated pneumonia in intensive care,144145 evidence for equivalent non-ventilator bundles in perioperative patient care to prevent PPCs is still uncertain 146. An international Delphi consensus process considered which interventions might best be combined to reduce PPCs,147 and a UK based, patient centred quality improvement project (ERAS+) used a PPC reduction care bundle with notable success 148. To date, these care bundles have predominantly included relatively simple and inexpensive interventions, often with imperfect evidence of efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to providing evidence for feasibility, the observed improvements in pulmonary function may provide a preventive health benefit. IMT has been used to prepare individuals for surgery and reduce instances of post-surgical pulmonary compromise, including pneumonia [29][30][31][32]. Additionally, Boswell-Ruys et al recently reported the results of a 6-week supervised RMT randomized clinical trial, which showed that individuals with SCI in the intervention group experienced significantly fewer respiratory complications in the following year than participants with SCI undergoing sham treatment [33].…”
Section: Discussionmentioning
confidence: 99%
“…The ACS best practice guidelines for PPC detailed risk factors and strategies to prevent complications. A 2018 expert survey including 362 respondents suggested a care bundle composed of factors before surgery, i.e., supervised exercise programs and inspiratory muscle training; factors during surgery, i.e., low tidal volume ventilation (6-8 ml/kg) with individualized positive end-expiratory pressure (PEEP) of 5-8 cmH 2 O and repeated recruitment maneuvers, use of routine monitoring to avoid hyperoxia, and efforts to limit neuromuscular blockade; and post-operative factors, i.e., deep breathing exercises and elevation of the head of the bed [115].…”
Section: Lung-protective Ventilationmentioning
confidence: 99%